Neuroleptic malignant syndrome - Huarcaya-Victoria, Jeff (2023)
The Neuroleptic malignant syndrome (NMS) is a potentially fatal adverse drug reaction commonly associated with antipsychotic medications. This article presents an updated review of NMS, addressing its epidemiology, risk factors, clinical presentation, possible underlying mechanisms, and treatment. The aim is to improve early recognition, diagnosis, and management of NMS in the Peruvian clinical setting to reduce morbidity and mortality. The literature search was conducted in PubMed, prioritizing randomized studies, systematic reviews, retrospective studies, and case reports. The incidence of NMS has decreased in recent years, possibly due to better medication prescription and titration. Risk factors include the use of high-potency antipsychotics, high doses, rapid dose escalation, and the use of depot injectable antipsychotics. Environmental factors such as dehydration, mechanical restraint, and extreme temperatures have been identified. Some psychopathological characteristics, such as psychomotor agitation and confusion, have also been associated with NMS. Genetic factors and genetic polymorphisms may influence susceptibility to NMS, but further studies are needed. The pathophysiology of NMS is related to excessive blockade of dopaminergic receptors, but other cofactors and neurotransmitter systems may be involved. The clinical presentation of NMS is characterized by changes in mental status, muscle rigidity, hyperthermia, catatonic symptoms, and profuse sweating. There are various treatment approaches ranging from general measures to pharmacological interventions.